Q-transform of distance distribution of binary equidistant codes and applications - XIA Shu-tao (Tongxin xuebao)
Q-transform of distance distribution of binary equidistant codes and equidistant constant weight codes were studied. By employing the properties of Q-transform, the maximum number of codewords of binary equidistant codes and equidistant constant weight codes were studied and two upper bounds were then obtained. These two bounds are better than previous known results in certain cases.